Определение оптимальных параметров материала солнечного элемента с нано размерными гетеро переходами по его световой вольтамперной характеристике (SCIENCE and SOCIETY, 2021)
The optimal ratios of the parameters of a solar cell with nano-dimensional hetero transitions that provide maximum power efficiency are determined. It follows from the obtained relations that a solar cell with nano-dimensional hetero transitions can be constructed in such a way that its efficiency will always have the required high level. It is shown that such a controlled situation is possible in relation to a solar cell with nano-dimensional p-n transitions created due to the phenomenon of self-organization on a substrate made of technical